Ecological industrialization and rural revitalization for global sustainable development - Yansui Liu; Xuhong Li; Sixin Su; Yuanzhi Guo (Geography and Sustainability)
Global sustainable development cannot be achieved by neglecting rural areas. These regions represent vast territorial spaces beyond urban built-up areas, possessing comparative advantages through their distinctive ecological resources. The transformation of ecological resources into economic value, commonly referred to as ecological industrialization, enhances rural economic vitality and developmental potential. Comprehensive rural revitalization strengthens regional functionality and development resilience, thereby promoting sustainable rural development. Based on human–earth system science, we theorize ecological industrialization as the PGR model, manifesting the transformation path from “poor mountain” to “green mountain” and then to “rich mountain”. It is noteworthy that in regions endowed with beautiful ecological landscapes, the PGR model prioritizes the transformation of “green mountain” to “rich mountain”. The essence of rural revitalization manifests through areal transformations driven by tripartite forces: the rural internal force, urban peripheral force, and urban–rural interaction force. There is a mutually reinforcing relationship between ecological industrialization and rural revitalization, and the implementation of the two can realize the coordinated development of rural functions. In this process, rural areas have realized the transformation from degraded land system to human–earth coupling system. Furthermore, through the examination of Fuping, Liuba, and Sanming as exemplary case studies, we have distilled three distinct modes of ecological industrialization: the circular industry mode, the ecological tourism mode, and the carbon sink trading mode. It is recommended that rural areas prioritize the coordinated implementation of ecological industrialization and rural revitalization in accordance with regional characteristics, so as to better foster rural sustainable development.